Mobile Phone Captives and Their Self-Redemption - Jing Jing; Yaoguo Ma (Computer Sciences & Mathematics Forum)
In modern society, people are becoming increasingly addicted to mobile phones, resulting in the alienation from objective real life and in people becoming captives of mobile phones. As the saying goes, since there is such a social phenomenon, there will inevitably be social reflection around it. Therefore, this article explores the reasons for the generation, maintenance forces, and coming difficulties of “mobile phone captives”, and explores some possible solutions and redemptions.